Role of CIA in MD5 to Optimize the Risk - Pramod Ganjewar; Pradhan, Padma Lochan (Journal of Network Security Computer Networks, 2026)
The MD5 (Message-Digest 5) hashing algorithm has been widely used for data integrity verification because of its high computational speed and low processing overhead. However, significant cryptographic weaknesses, particularly collision attacks, have rendered MD5 unsuitable for modern security-critical applications. This study evaluates MD5 using the CIA Triad framework—Confidentiality, Integrity, and Availability—and examines its impact on organizational risk optimization within the context of the NIST Risk Management Framework (RMF). The analysis shows that MD5 fails to ensure data integrity because attackers can generate different inputs that produce the same hash value, enabling data forgery and manipulation. From a confidentiality perspective, MD5’s rapid computation makes it vulnerable to brute-force and dictionary attacks when used for password storage. Additionally, continued reliance on MD5 can negatively affect system availability due to compliance restrictions, software incompatibilities, and the rejection of weak cryptographic standards in modern security infrastructures. Despite these limitations, MD5 retains limited utility in low-risk, high-performance environments where cryptographic security is not the primary objective, such as file checksums, duplicate detection, and error verification. To optimize security risk, this study recommends a tiered cryptographic approach in which integrity-critical applications migrate to stronger hashing algorithms such as SHA-256 or SHA-3, while password protection employs adaptive hashing techniques such as bcrypt or Argon2. The findings conclude that MD5 should be deprecated for security-sensitive functions but may remain appropriate for non-adversarial operational tasks. This balanced approach enhances confidentiality, integrity, and availability while maintaining performance and supporting regulatory compliance in contemporary cybersecurity environments.